Acid‐catalysed glucose dehydration in the gas phase: a mass spectrometric approach. (January 2015) - Ricci, Andreina; Di Rienzo, Brunella; Pepi, Federico; Troiani, Anna; Garzoli, Stefania; Giacomello, Pierluigi
<x xml:space="preserve">Abstract</x> Understanding on a molecular level the acid‐catalysed decomposition of the sugar monomers from hemicellulose and cellulose (e.g. glucose, xylose), the main constituent of lignocellulosic biomass is very important to increase selectivity and reaction yields in solution, key steps for the development of a sustainable renewable industry. In this work we reported a gas‐phase study performed by electrospray triple quadrupole mass spectrometry on the dehydration mechanism of d‐glucose. In the gas phase, reactant ions corresponding to protonated d‐glucose were obtained in the ESI source and were allowed to undergo collisionally activated decomposition (CAD) into the quadrupole collision cell. The CAD mass spectrum of protonated d‐glucose is characterized by the presence of ionic dehydrated daughter ion (ionic intermediates and products), which were structurally characterized by their fragmentation patterns. In the gas phase d‐glucose dehydration does not lead to the formation of protonated 5‐hydroxymethyl‐2‐furaldehyde, but to a mixed population of m/z 127 isomeric ions. To elucidate the d‐glucose dehydration mechanism, 3‐O‐methyl‐d‐glucose was also submitted to the mass spectrometric study; the results suggest that the C3 hydroxyl group plays a key role in the reaction mechanism. Furthermore, protonated levulinic acid was found to be formed from the monodehydrated d‐glucose ionic intermediate, an alternative pathway other than the known route consisting of 5‐hydroxymethyl‐2‐furaldehyde double hydration. Copyright © 2015 John Wiley & Sons, Ltd.